Bradycardia associated with ALK inhibitors in the treatment of non-small cell lung cancers: a systematic review and meta-analysis. (14th October 2021) - Zhou, S; Cirne, F; Kappel, C; El-Kadi, A; Ellis, P; Leong, D P
Abstract: Introduction: Anaplastic Lymphoma Kinase (ALK) inhibitors represent a major therapeutic advance in the treatment of ALK-rearranged non-small cell lung cancer (NSCLC). Bradycardia was initially observed with crizotinib, the first ALK inhibitor. The risk of bradycardia and whether it differs among various generations of ALK inhibitors has not been systematically described. Purpose: The primary objective of this systematic review is to compare the risk of bradycardia in patients who received an ALK inhibitor or standard chemotherapy for the treatment of NSCLC in randomized controlled trials. Methods: We conducted a systematic literature search in MEDLINE, EMBASE, Cochrane Central, Web of Science, and Clinical Trials registry. We included randomized controlled trials that compared two different ALK inhibitors, or an ALK inhibitor with standard chemotherapies in patients with NSCLC. The primary outcome of interest was the number of bradycardia events. Because bradycardia was not systematically reported in many trials, we also documented reports of dizziness (as a potential symptom of bradycardia) in a secondary analysis. Results: We identified 12 eligible studies including 2915 participants. Bradycardia was reported as a treatment-emergent adverse event in 9 trials; dizziness was reported in the remaining 3 trials. The type of bradycardia and use of heart rate-slowing medications were not documented in most studies. The incidence of bradycardia among 1080 individuals prescribed crizotinib in 8 trials was 13% (95% CI 9–17%) during a mean follow-up of 1.26 years. A meta-analysis of four trials that compared crizotinib with standard chemotherapies (Figure 1) showed a higher risk of bradycardia with crizotinib (RR 19.33; 95% CI 5.40–69.22). Newer generations of ALK inhibitors (alectinib, brigatinib and lorlatinib) showed similar rates of bradycardia compared to crizotinib (RR 0.51; 95% CI 0.21–1.26; Figure 2). Dizziness was more common in ALK inhibitors than standard chemotherapies (RR 1.83; 95% CI 1.38–2.42). Conclusions: Our findings suggest that crizotinib is associated with a higher rate of bradycardia than standard chemotherapies, while no difference was found between crizotinib and newer generations of ALK inhibitors. The higher rate of dizziness in ALK inhibitors could represent a symptom of bradycardia. Further research is needed to evaluate the incidence and types of ALK inhibitor-associated bradycardia and its relationship with patient symptoms. FUNDunding Acknowledgement: Type of funding sources: None.